Acute toxicity and ethological responses of oligochaete worm Tubifex tubifex (Muller) exposed to a cationic surfactant Cetylpyridinium chloride - Bhattacharya, Ritwick; Chatterjee, Arnab; Saha, Nimai Chandra (International Journal of Scientific Research in Biological Sciences, 2019)
Cetylpyridinium chloride is a quaternary cationic surfactant which exhibit broad spectrum antimicrobial activity. The present study was conducted to evaluate the acute toxicity of Cetylpyridinium chloride to a benthic oligochaete worm Tubifex tubifex in terms of LC50 and behavioral responses. All experiments were conducted, in a static bioassay system, using increasing concentrations of Cetylpyridinium chloride for 96 h duration. The LC50 values associated with 95% lower and upper confidence limits for the surfactant were determined statistically using Finney’s Probit Analysis Method developed by EPA and were found to be 0.330 (0.305-0.357) ppm, 0.305 (0.280-0.332) ppm, 0.225 (0.204-0.248) ppm and 0.213 (0.190-0.240) ppm at 24, 48, 72 and 96 hours exposure respectively. The results of regression analysis indicated that the mortality rate varied significantly (p<0.05) with the increasing concentrations of surfactant. In addition, the aquatic worm exhibited abnormal behavioral responses like hyperactivity, decreased clumping tendency, increased mucous secretion and wrinkling effect on increasing concentrations of toxicant and period of exposure. Thus, these findings can be used as a potential tool for creating awareness among people to limit the misuse of household products containing surfactants.